Plurality of religions in a (post-)secular society. Transformations - challenges - learning processes - Gmainer-Pranzl, Franz (Momentum Quarterly, 2018)
For Austria it was a long and difficult way to become a religiously pluralistic society, not least because of special religious-political developments. The official recognition of the Islamic Community in 1979 is the beginning of religious plurality in Austria which increased in the last decades. If religious multiplicity can really help to develop an open society depends also on the concept of “religion” which one presumes, on the specific religious-political options or on theological models which see religious plurality differently. Religions are able to initiate societal learning processes, for example concerning the exchange with strangers or social competence. However, this learning process needs political support in the field of education or inclusion.